Jammu and Kashmir Annual Plan 1965-66 - Planning Commission (Planning Commission, 1964)
Summary statement of State Plan outlay for 1965-66 Planning Department Jammu & Kashmir State Development of Local Manorial Resources Extension of Laboratory Development of Research sub Station Jammu. Research on Grass and Fodder Research on species and condiments Development of Fruits production Agriculture Statistics Extension and Strengthening of crop estimation survey Weed control scheme.
Planning Department Jammu & Kashmir State
Planning Department Jammu & Kashmir
Keywords: Summary statement of State Plan outlays for 1965-66; Agricultural Production; Minor Irrigation; Soil Conservation; Animal Husbandry; Dairying and Milk Supply; Forests; Cooperation and Community Development; Community Development and National Extension Service; Metric System of Weights and Measures; Area Development; Information and Publicity.